Modular architecture of a non-contact pinch actuation micropump - Chee, Pei Song; Rashidah, Arsat. Dr.; Tijjani Adam, Shuwa; Uda, Hashim, Prof. Dr.; Ruzairi, Abdul Rahim, Prof. Dr.; Leow, Pei Ling (MDPI, Basel, Switzerland., 2013)
Link to publisher's homepage http://www.mdpi.com/